Upcoming: Undergraduate Student Perspective on Teaching Assistants - Jade E. Carriero; Bernard P. Gee (Journal of the Scholarship of Teaching and Learning)
Having access to teaching assistants (TAs) in college classrooms has been shown to be beneficial for student performance. Past research has used surveys and observed student-TA interactions to measure their effectiveness, featuring primarily graduate student TAs. The present research was designed to gain insight into how students perceive and utilize their undergraduate TAs. Additionally, it examined TA responsibilities and interactions outside the classroom that previous research does not address in depth. Undergraduate students were asked to complete an online survey divided into three categories: TA profile, interactions with the TA, and TA benefits. Survey results revealed that students felt comfortable asking their TA for assistance. However, the majority of participants reported not utilizing their TAs as much as they wanted due to an unawareness of how to access them. Students who did utilize their TAs found them to be very beneficial as they aided in reviewing the course material and provided useful study tips. Overall, the findings provided insight on how to optimize the role and responsibilities of a TA to increase student engagement and improve their effectiveness in addressing students’ academic needs.